2006
DOI: 10.1002/cncr.21678
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum level of YKL‐40 is an independent prognostic factor for poor survival in patients with metastatic melanoma

Abstract: BACKGROUNDYKL‐40 is a growth factor for connective tissue cells and stimulates migration of endothelial cells. Cancer cells, macrophages, and neutrophils secrete YKL‐40. Its function in cancer is unknown. High serum YKL‐40 levels have been associated with a poor prognosis in patients with several solid tumors. The prognostic impact of serum YKL‐40 in metastatic melanoma was evaluated.METHODSYKL‐40 was measured in serial serum samples from 110 patients with metastatic melanoma obtained immediately before and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 41 publications
(2 reference statements)
3
94
2
2
Order By: Relevance
“…1 Both tumor cells and tumor-associated macrophages produce YKL-40. 2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population.…”
mentioning
confidence: 99%
“…1 Both tumor cells and tumor-associated macrophages produce YKL-40. 2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population.…”
mentioning
confidence: 99%
“…Blood levels of CHi3L1 are negligible under normal physiologic conditions, however, elevated blood levels of CHi3L1 have been found in patients with chronic inflammatory conditions [25] and a wide variety of cancers including colorectal [22,26] , breast [27] , prostate [28] , lung [29,30] , thyroid [31] , endometrial [32] pancreatic [33] hepatocellular [34] , ovarian [35] , gastric cancer [36] , and malignant melanoma [37] . Additionally, for the majority of these malignancies, a correlation has been demonstrated between blood levels of CHi3L1 and a poor prognosis [26,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Also, increased expression of CHi3L1 in CRC has been shown to be strongly associated with increased microvascular density [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Serum YKL-40 has been shown to be a helpful diagnostic and prognostic indicator in various types of cancers, which include colorectal, 19 breast, 20 lung, 21 head and neck, 22 prostate, 23 ovarian cancer, 24 and malignant melanoma. 25 Depending on the tumor type, the effect of serum YKL-40 on survival rates may be substantial (hazard ratio range, 1.3-4.1). 26 Most recently, a Danish cohort study showed that elevated YKL-40 level predicts the increased risk of gastrointestinal cancer and decreased survival after cancer diagnosis in general population.…”
Section: Discussionmentioning
confidence: 99%